A feasibility study on integrating large-scale battery energy storage systems with combined cycle power generation – Setting the bottom line. (15th October 2019) - Nian, Victor; Jindal, Gautam; Li, Hailong
Abstract: Strong attention has been given to the costs and benefits of integrating battery energy storage systems (BESS) with intermittent renewable energy systems. What's neglected is the feasibility of integrating BESS into the existing fossil-dominated power generation system to achieve economic and environmental objectives. In response, a life cycle cost-benefit analysis method is introduced in this study taking into consideration three types of battery technologies, namely, vanadium redox flow battery, zinc bromine flow battery, and lithium-iron-phosphate battery. The objective is to evaluate the life cycle carbon emissions and cost of electricity production by combined cycle power generation with grid-connected BESS. Findings from the Singapore case study suggest a potential 3–5% reduction in the life cycle carbon emission factors which could translate to a cumulative carbon emission reduction of 9–16 million tonnes from 2018 to 2030 from electricity generation. Grid-connected BESS could reduce the levelized cost of electricity by 4–7%. A synergistic planning of CCGT and BESS could theoretically reduce the system level power generation capacity by 26% albeit a potential increase in the overall capital cost at the current cost of batteries. The projected battery cost reduction is critical in improving the feasibility of large-scale deployment. Highlights: Life cycle cost benefit analysis of combined cycle gas turbine with battery storage. Stationary battery storage can decarbonize fossil fuelled power generation. Battery storage can reduce the system-level cost of the electricity sector.